Green manure in parsley production and soil fertility in Piracicaba, Brazil - Costa-Mello, Simone da; Nimi-Kassoma, Josina; Quesada-Roldán, Gustavo; Dantas-da Silva, Adriano; Donegá, Mateus Augusto; Santos-Dias, Carlos Tadeu dos (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Green manure has been employed successfully in vegetable production as a nitrogen source and for soil conditioning, especially in highly, intensively prepared soils. However, the information on the effects in parsley culture is very limited. The green manure species Mucuna deeringiana, Crotalaria juncea and Crotalaria spectabilis were studied for the physical and chemical soil properties and yield of two cultivars of parsley (Lisa Preferida and Graúda Portuguesa). Two experiments were conducted at the Crop Production Department at the Escola Superior de Agricultura “Luiz de Queiroz”, Piracicaba-SP, Brazil. The soil physical properties, such as density, total porosity, macro and microporosity, were not affected by green manure, as compared to the control in both experiments. The chemical properties (pH, organic matter and nutrients content) only changed in the second experiment, significantly increasing the Ca and P concentration and bases sum with the green manure. In soils with high fertility, such as the one in this study, it is difficult to find benefits from a single green manure. The parsley yield increased on average 61% after green manure cultivation, as compared to the control (14.9 t ha-1), regardless of the green manure species used, only in the first experiment. In the second experiment, the parsley yield did not increase because of the green manure effects, as compared to the control, possibly because, in this cycle, the produced green manure biomass and the parsley yield were affected by abiotic conditions.